ABRATION AND EROSION WEAR TEST USING PIN ON DISK AND AIR JET EROSSION METHODS ON A356 ALUMINIUM - Khairina Izzati, Tiya
Abrasion and erosion are one of the most common types of wear on components that rub against each other. An engine block is one of the components that rub against each other and is prone to wear and tear, making wear resistance a critical parameter in the design and manufacture of the engine block itself. The use of aluminum as the base material for engine blocks has begun to be widely used because of its high strength-toweight ratio. So, it is important to know the wear resistance of both abrasion and erosion in aluminum alloys. In this study, abrasion testing was carried out using pin on disk and erosion using air-jet erosion. Abrasion testing is carried out by varying the lubrication and type of powder. In the erosion test, variation of the impact angle is used. The results of this test are in the form of mass change values before and after the test: the smaller the mass reduction value that occurs, the better the wear resistance. From the results of the pin on disk testing, it was found that using lubricants with a higher viscosity will result in better wear resistance, while using abrasive powders that are hard and tend to have an angular shape will cause more severe wear. Meanwhile, the air jet erosion test found that using a powder impact angle of 90° will result 55% less wear than using a powder impact angle of 15°. The difference occurs because of the different erosion modes on the sample surface with different impact angles. At a relatively small angle 15°, the mode of erosion that occurs is cutting, while at a relatively large angle 90°, the mode of erosion is a rebound.